REGULATORY SYNCHRONIZATION BETWEEN INDONESIA'S PERSONAL DATA PROTECTION LAW AND THE ELECTRONIC INFORMATION AND TRANSACTIONS LAW IN THE CORETAX SYSTEM - Winatrisia; Hanuring Ayu Ardhanu Putri; Ida Aryati Dyah Purnomo Wulan (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The rapid development of information technology has encouraged the digital transformation of public administration, including the taxation sector in Indonesia. As part of tax administration reform, the Directorate General of Taxes has implemented the Coretax Administration System (Coretax), an integrated digital platform designed to enhance efficiency, transparency, and accountability in tax administration. The system processes and manages large volumes of taxpayers’ personal data, including identity information, financial records, business transactions, and tax compliance history. Consequently, ensuring the legal protection of personal data has become a critical issue. This study aims to analyze the regulatory synchronization between Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) and the Electronic Information and Transactions Law (ITE Law) in the implementation of the Coretax system. The research employs a normative legal method using statutory and conceptual approaches. The findings indicate that although the PDP Law functions as a lex specialis governing personal data protection and the ITE Law serves as a lex generalis regulating electronic systems, potential regulatory disharmony remains regarding the scope of regulation, data protection mechanisms, and law enforcement procedures. Such inconsistencies may create legal uncertainty and weaken the effectiveness of taxpayers’ personal data protection within the Coretax system. Therefore, comprehensive regulatory harmonization is necessary through the alignment of legal norms, strengthening supervisory institutions, and implementing integrated data security standards. These measures are essential to ensure legal certainty and effective protection of taxpayers' personal data rights in Indonesia’s digital taxation ecosystem.